New orchids in the flora of Vietnam VIII (Orchidaceae: Epidendroideae, tribes Malaxideae, Neottieae and Podochileae) - Averyanov, Leonid V.; Nguyen, van Canh; Vuong, Truong Ba; Nuraliev, Maxim S.; Nguyen, Khang Sinh; Maisak, Tatiana V.; Yudova, Daria A.; Saidov, Nikita T.; Nguyen, Cuong Huu; Nong, Duy Van (Phytotaxa, 2024)
The paper presents new data on the orchid diversity of Vietnam obtained mainly in the course of the fieldwork in 2020–2023, as well as from the investigation of the collections stored at the Herbaria of Russia and Vietnam. It includes descriptions of four species (Appendicula spicata, Dendrobium khanhii, D. vietii, Listera anthropophora) and one variety (Eria dacrydium var. cornuta) new to science, as well as reports of 18 species new to the flora of Vietnam (Bulbophyllum conchiferum, B. gibbosum, B. lasiochilum, B. malleolabrum, B. medusae, B. mucronatum, B. reclusum, B. siamense, B. sutepense, Dendrobium deltatum, D. densiflorum, D. lampongense, D. polyanthum, Oberonia maxima, Phreatia sulcata, Podochilus lucescens, Sunipia grandiflora and S. rimannii). In addition, a new name, Dendrobium nobile var. luteoalbum, and a new nomenclatural combination, Eria chienii, are proposed, and lectotypes for the names Bulbophyllum mucronatum, B. sutepense, Dendrobium deltatum and D. nobile var. luteoalbum are designated. For each of the studied species, relevant synonyms, studied specimens, ecology, phenology, distribution, conservation status assessment according to the IUCN Red List Categories and Criteria, brief taxonomic notes, and illustrations are provided. For the newly described taxa, morphological descriptions and notes on etymology are included.